An Analysis of Organizational Support and Work-Life Balance and Their Impact on Turnover Intention (A Qualitative Study of Teachers at RA Al-Idhar) - Shinta Indrie Nurmalatifah; Mochamad Vrans Romi (LP2M IAIN Palopo, 2026)
This study examines the influence of organizational support and work-life balance on turnover intention among teachers at RA Al-Idhar. In an educational setting, organizational support and work-life balance are important factors that can influence teachers’ comfort, job satisfaction, and desire to remain with the organization. This study aims to understand how organizational support and work-life balance influence the emergence of turnover intention among teachers at RA Al-Idhar. This study employed a qualitative approach, utilizing data collection techniques such as interviews, observation, and documentation. The informants in this study consisted of the school principal, teachers, and the teachers’ husbands. The results indicate that organizational support at RA Al-Idhar is considered quite good, as evidenced by effective communication, family-like working relationships, and the availability of work flexibility under certain conditions. Teachers’ work-life balance was also rated as fairly good in terms of time management and work flexibility; however, challenges were still identified regarding mental and physical health due to workloads and limited workplace facilities. These conditions give rise to turnover intentions, as evidenced by teachers’ thoughts of seeking other jobs, searching for job openings, and even wanting to leave the organization. This study shows that organizational support and work-life balance play a significant role in influencing teachers’ turnover intentions. The findings of this study are expected to serve as a basis for educational institutions to improve workplace comfort and teacher well-being, as well as to retain teaching staff so that turnover intentions can be minimized